Macroeconomic Aspects of Oil Price Increases - Dohner, Robert S. (Tufts Archival Research Center, 2005)
Volume 4, Issue 2. Summer The unprecedented flow of dollars to the oil-producing countries since the 1973 oil price rises has caused major strains in the economies of the consuming countries. Numerous economists have attempted to analyze the effects, both good and bad, of energy price changes, and to propose solutions. In the following paper, Professor Dohner examines the macroeconomic consequences, concentrating on the situation in the United States, but with an analysis applicable to other industrialized countries as well.